Assessment of Indicators of the Circular Economy on the Example of the Countries of the European Union and the Possibility of Application in the Conditions of Kazakhstan - A. M. Tleppayev; S. Zh. Zeinolla (Экономика: стратегия и практика, 2021)
The purpose of this study is to study the approaches to measuring the indicators of the circular economy used in the countries of the European Union and in the OECD countries to form an understanding of the applicability of the presented methods. The study used the methods of econometric modeling, statistical and comparative analyzes. A model was built using data for the European Union countries, the following variables (factors) were used to build this model: the share of material extracted and returned to the economy, the intensity of CO2 emissions, the level of energy intensity of primary energy, GDP per capita, research and development costs, the share urban population in total. Based on the simulation results, it was concluded that GDP growth and growth in energy intensity, together with an increase in the level of technology in the economy, leads to an increase in the processing of materials and their reuse in economic circulation. The results of modelling confirm the conclusions of the previous authors, the analysis of the strategies of the EU and OECD countries. It is necessary to invest more financial resources in R&D, development of new technologies and innovations for achieve better results. Greater involvement of consumers and businesses in activities conducive to the circular economy is also critical. Achieving these two goals will contribute to sustainable economic development. Based on the analysis of the model and strategies of the OECD and EU countries on the circular economy, we concluded that international innovations in the circular economy are applicable to Kazakhstan’s economy.